Mapping of Livable and Unlivable Houses for the Priority of House Rehabilitation Beneficiaries in Sambiduwur Village, Tanon District, Sragen Regency - Ramadhanty, Dhea Fina; Yesiana, Reny; Astuti, Khristiana Dwi (Universitas Negeri Semarang, 2024)
Houses are one of the basic needs of humans. A home is a place for humans to live and shelter from climate and weather’s influence. As mandated in Pasal 28 H Amandemen Undang - Undang Dasar1945, a house is the fundamental right of the people, so every citizen has the right to get a place to live in a good and healthy environment. The citizens’ economic unpreparedness makes many Indonesians still live in unlivable houses. Based on BPS data, in 2010, there were 40.46% unlivable houses in urban and rural areas. For this reason, the Government continues to strive and protect the community so that they can live in appropriate places. The Government’s desire to improve the socioeconomic level of low and middle-income people is demonstrated through the social rehabilitation program for housing. The limited availability of data on unlivable housing makes it difficult for the Government to determine the social beneficiary’s priority. This study aims to map the livable and unlivable houses to determine the beneficiary’s importance in Sambiduwur Village. The primary data collection method used was observing the house in Sambiduwur Village. The analysis technique used identified livable and unlivable houses with scoring which refers to the criteria and indicators from the module issued by the Minister of Public Works and Housing. Determination of the level of damage to the house is guided by Appendix V, Regulation of Minister No.33/Prt/M/2016, about Technical Instructions for The Implementation of Special Allocation Funds for Infrastructure. The study results showed that 979 houses in Sambiduwur Village, 79 (8.06%) houses were classified as unlivable, and 900 (91.94%) houses were classified as livable.